Metric Culture 2018
DOI: 10.1108/978-1-78743-289-520181008
|View full text |Cite
|
Sign up to set email alerts
|

Doing Calories: The Practices of Dieting Using Calorie Counting App MyFitnessPal

Abstract: He works in the areas of Science & Technology Studies (STS) and Human-Computer Interaction (HCI), where he uses ethnomethodology and conversation analysis to study scientific work and new technologies 'in use'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
(19 reference statements)
1
7
0
1
Order By: Relevance
“…Accounts of discerning work and partial data return a degree of agency to users of self-tracking technologies in the creation and circulation of data, while being attentive to the constraints imposed by the diverse materialities involved. Like others (Didžiokaitė et al 2018;Lomborg et al 2018; Esmonde 2020; Gorm and Shklovski 2019), we have shown that, even where people do record their data in ways that might be compiled by third parties (i.e. through apps), they do not necessarily give up all their data, and may be selective in what they record.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Accounts of discerning work and partial data return a degree of agency to users of self-tracking technologies in the creation and circulation of data, while being attentive to the constraints imposed by the diverse materialities involved. Like others (Didžiokaitė et al 2018;Lomborg et al 2018; Esmonde 2020; Gorm and Shklovski 2019), we have shown that, even where people do record their data in ways that might be compiled by third parties (i.e. through apps), they do not necessarily give up all their data, and may be selective in what they record.…”
Section: Discussionsupporting
confidence: 77%
“…(Ayo, 33, university researcher, black African) Ayo's account again underscores the affective resonance of self-monitoring records, which have the capacity to make her "sad" if they go in the wrong direction. This chimes with studies of calorie and fitness tracking (Didžiokaitė et al 2018;Esmonde 2020;Gorm and Shklovski, 2019).…”
Section: Discerning Work and Partial Datamentioning
confidence: 70%
See 2 more Smart Citations
“…Research shows that self-tracking technology can facilitate learning insights about one's body and mind (Choe et al 2014); function as triggers for action (Ajana 2017); give a "nudge;" (Lupton 2014) or play the role of an authority that shows the persuasive effect (Fogg 2002). Users also divert themselves from the projection of technology, finding meanings or engaging in negotiations (Ruckenstein and Schüll 2017;Lomborg et al 2018;Didžiokaitė et al 2018).…”
Section: Monitoring Health As a "Self-centered" Practicementioning
confidence: 99%